Tissue-Based Biomarkers for the Risk Stratification of Men With Clinically Localized Prostate Cancer - Basourakos, Spyridon P.; Tzeng, Michael; Lewicki, Patrick J.; Patel, Krishnan; Al Hussein Al Awamlh, Bashir; Venkat, Siv; Shoag, Jonathan E.; Gorin, Michael A.; Barbieri, Christopher E.; Hu, Jim C. (Frontiers in Oncology, 2021)
Risk stratification of men with clinically localized prostate cancer has historically relied on basic clinicopathologic parameters such as prostate specific antigen level, grade group, and clinical stage. However, prostate cancer often behaves in ways that cannot be accurately predicted by these parameters. Thus, recent efforts have focused on developing tissue-based genomic tests that provide greater insights into the risk of a given patient’s disease. Multiple tests are now commercially available and provide additional prognostic information at various stages of the care pathway for prostate cancer. Indeed, early evidence suggests that these assays may have a significant impact on patient and physician decision-making. However, the impact of these tests on oncologic outcomes remains less clear. In this review, we highlight recent advances in the use of tissue-based biomarkers in the treatment of prostate cancer and identify the existing evidence supporting their clinical use.